Psychosocial Factors and Prevalence of Stress in Early Pregnancy: A Study in Makassar City - Jumriani Ansar; Asri C Adisasmita; Sudarto Ronoatmodjo; Farid Husin; Muliani Ratnaningsih (Media Kesehatan Masyarakat Indonesia, 2025)
Stress during pregnancy can negatively impact the health of both the mother and the fetus, especially in the first trimester, which is a period of intense physical and emotional adaptation. This study aims to determine the prevalence and psychosocial factors associated with the occurrence of stress in first-trimester pregnant women in Makassar City. This study uses a cross-sectional design involving 256 first-trimester pregnant women from five public health centers in the suburban areas of Makassar City. Data were collected through interviews using a structured questionnaire. The Edinburgh Postnatal Depression Scale (EPDS10) instrument was used to measure stress levels. Analysis was conducted bivariately and multivariately using logistic regression. The prevalence of severe stress among pregnant women in the first trimester was 36.72%. Multivariate analysis revealed two factors significantly associated with severe stress: low family income (adjusted Prevalence Ratio (aPR) = 2.32; 95% CI: 1.15–4.66; p = 0.018) and poor interpersonal relationships with parents or in-laws (adjusted Prevalence Ratio (aPR) = 4.63; 95% CI: 1.53–14.02; p = 0.007). Socioeconomic factors and interpersonal relationships with parents/in-laws influence the high levels of stress experienced by first-trimester pregnant women. Early intervention that considers the family's economic aspects and social support from the surrounding environment is critical in preventing stress during pregnancy.